PERANCANGAN PROSES AKUNTANSI BERBASIS GOOGLE SPREADSHEET UNTUK PENYUSUNAN LAPORAN KEUANGAN SESUAI SAK EMKM : (STUDI KASUS UMKM JAGOAN AYAM GEPREK) - Savano, Dini Oktafia; Bidhari, Sandhika Cipta (Politeknik Negeri Ambon, 2025)
Introduction: This research aims to develop an accounting workflow using Google Spreadsheet that aligns with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), specifically adapted to support the operational needs of UMKM Jagoan Ayam Geprek. The need arises due to the demand for standardized financial reporting to improve accountability, transparency, and access to funding sources among MSMEs.Methods: This study employs a qualitative descriptive method using the System Development Life Cycle (SDLC) framework. The feasibility of the proposed system is analyzed through the TELOS approach, which encompasses Technical, Economic, Legal, Operational, and Schedule aspects. Data is collected through interviews, observations, and documentation, reinforced with triangulation to ensure validity.Results: The results indicate that the proposed system, built using Google Spreadsheet, effectively facilitates the entire accounting process, from transaction entries to generating financial reports that comply with SAK EMKM standards. Furthermore, the system is considered feasible and applicable across all TELOS aspects and offers an accessible, efficient, and user-oriented solution even for users without prior accounting knowledge. Keywords: Financial Accounting Standards for MSMEs, Accounting Process, Google Spreadsheet